Maturidade da cultura de segurança do trabalho em uma instituição federal de ensino - Mateus, Cássia Cristina da Silva (2024)
In Brazil, until 1990, there were no specific regulatory measures for the health of public servants. Only in 2009 did the Policy of Attention to the Health of Federal Public Servants (PASS) emerge, encompassing a series of aspects related to the health of the servants. In this context, the focus of this investigation lies in the maturity of the Safety Culture in Federal Institutes of Education. The research question guiding this study seeks to understand the maturity stage of the safety culture in a federal educational institution. To this end, the research adopted a quantitative, exploratory, and descriptive approach, targeting federal public servants working at the Federal Institute of Education, Science, and Technology of Ceará. The research was conducted with the active federal public servants of the Federal Institute of Education, Science, and Technology of Ceará, which has 34 units in 32 municipalities, totaling 3569 servants. Data collection was carried out through an adapted online questionnaire, and the analysis included qualitative techniques, such as the analysis of the degree of agreement of the variables for the evaluation of the maturity stage, and quantitative techniques, such as the Cronbach's Alpha Coefficient test and exploratory factor analysis. The work is structured into five sections: introduction, theoretical framework, methodology, study findings, and final considerations. The results indicate an overall reactive maturity stage, with no significant differences between teachers and administrative technicians. However, between the macro regions 04 and 05, which are further from the headquarters, a more pronounced degree of disagreement was observed. The factors categorized with the lowest degree of maturity were communication, commitment, and involvement. The factor analysis pointed to five factors explaining the degree of maturity, as did the adopted model. However, the model variables were reorganized into factors by correlation, with variable E3 (Means of information) being eliminated for not reaching a satisfactory factor load. This research contributed to the deepening of the theoretical and empirical framework of the adopted evaluation model, proposing improvements in the maturity stage assessment scale. Furthermore, it offers new perspectives for organizational improvements, identifying opportunities for enhancement in the institution's safety culture. Socially, it provides support for defining strategic actions that impact the satisfaction of the servants regarding their working conditions.